Urinary excretion profile of methiopropamine in mice following intraperitoneal administration: A liquid chromatography–tandem mass spectrometry investigation. Issue 1 (7th August 2020) - Camuto, Cristian; Pellegrini, Sheila; De‐Giorgio, Fabio; de la Torre, Xavier; Marti, Matteo; Mazzarino, Monica; Botrè, Francesco
Abstract: We have considered the urinary excretion profile of methiopropamine (MPA), a thiophene ring‐based structural analog of methamphetamine with similar stimulant effects, with the aim of selecting the most appropriate marker(s) of intake that may be useful in forensic analysis. For this purpose, in vitro studies were preliminarily performed on human liver microsomes for tracing the phase I metabolic pathways of MPA, preselecting the best candidates as potential target analytes, and designing the optimal experimental strategy. In vivo studies were then conducted on mice, after the intraperitoneal administration of a 10‐mg/kg dose. Urine samples were collected every 3 h in the first 9 h and, subsequently, from 24 to 36 h, and stored at –80°C until further analysis. The measurements were performed using a targeted procedure based on liquid/liquid extraction followed by liquid chromatography–tandem mass spectrometry analysis. Our results show that in the time interval 0–9 h after administration, MPA was extensively oxidized mainly to nor‐MPA, oxo‐MPA, and two hydroxylated metabolites (ie, hydroxy‐aryl‐methiopropamine and hydroxy‐alkyl‐methiopropamine). All phase I metabolites underwent phase II metabolism, with the formation of nor‐hydroxy‐methiopropamine only in phase II, confirmed by the results obtained after enzymatic hydrolysis with β ‐glucuronidase and arylsulfatase. In the time interval 24–36 h after administration, only unchanged MPA and nor‐MPA were detected, suggesting that these two markers are those endowed with the highest diagnostic value. The method was validated for these two principal markers, proving to be fit for anti‐doping, toxicological, and forensic analyses. Abstract : The present work evaluated the urinary excretion profile of methiopropamine (MPA) in a range of 0–9 and 24–36 h after the injection of a 10‐mg/kg dose of MPA in mice. MPA underwent N‐ demethylation, hydroxylation, and oxidation. MPA and nor‐MPA are the most informative markers of intake.